2012
DOI: 10.2106/jbjs.k.00926
|View full text |Cite
|
Sign up to set email alerts
|

Talocalcaneal Tarsal Coalitions and the Calcaneal Lengthening Osteotomy: The Role of Deformity Correction

Abstract: It is generally accepted that resection is the treatment of choice for an intractably painful small talocalcaneal tarsal coalition that is associated with a wide, healthy posterior facet and minimal valgus deformity of the hindfoot. Although triple arthrodesis has been recommended for those who do not meet all three criteria, the present study suggests that an algorithmic treatment approach is justified. Treatment of the valgus deformity appears to be as important as that of the coalition. Calcaneal lengthenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 39 publications
(85 reference statements)
1
87
0
5
Order By: Relevance
“…12,[16][17][18] Mosca and Bevan 16 advocate that any patient with hindfoot valgus of >16 degrees or large subtalar coalition should undergo a calcaneal lengthening osteotomy, and the average AOFAS score in their small series of 8 patients was 91.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[16][17][18] Mosca and Bevan 16 advocate that any patient with hindfoot valgus of >16 degrees or large subtalar coalition should undergo a calcaneal lengthening osteotomy, and the average AOFAS score in their small series of 8 patients was 91.2.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Historically, patients with a TC coalition and >50% involvement of the joint were recommended for fusion over excision. 12,[16][17][18] More recently, authors have demonstrated success with excision regardless of the extent of the coalition. 14,15 At the present time, symptomatic tarsal coalitions (both CN and TC) are typically treated with coalition resection and interposition to prevent recurrence.…”
mentioning
confidence: 99%
“…7-14 Despite these positive results, some question the value of resection for TC coalitions involving >50% of the subtalar joint or with concomitant valgus deformity. [17][18][19] Others, however, have reported success in patients with coalition involving >50% of the subtalar joint. 8,20 One potential cause of variation in TC resections compared with the more accepted CN resections is the difficulty visualizing the middle facet of the TC joint on plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Their series of patients who underwent both a lateral column lengthening through the calcaneus and an Achilles lengthening had excellent results with pain relief and deformity correction. 36 Others have reported the use of a subtalar arthroereisis to restore the alignment of the calcaneus and talus following resection. 37 Although the data are limited to a small number of level IV …”
Section: Operative Treatmentmentioning
confidence: 99%